Influence of Preoperative Tunnel Widening On the Outcomes of a Single Stage–Only Approach to Every Revision Anterior Cruciate Ligament Reconstruction: An Analysis of 409 Consecutive Patients From the SANTI Study Group. Issue 6 (May 2021) - Pioger, Charles; Saithna, Adnan; Rayes, Johnny; Haidar, Ibrahim M.; Fradin, Thomas; Ngbilo, Cedric; Vieira, Thais Dutra; Cavaignac, Etienne; Sonnery-Cottet, Bertrand
Background: Preoperative tunnel widening is a frequently reported indication for performing a 2-stage revision anterior cruciate ligament reconstruction (ACLR) instead of a single-stage procedure. However, the strength of the available evidence to support a 2-stage strategy is low. Purpose/Hypothesis: The purpose was to evaluate the clinical outcomes of a single stage–only approach to revision ACLR. It was hypothesized that this approach would be associated with significant improvements from baseline in patient-reported outcome measures (PROMs) and knee stability and that there would be no significant differences in any postoperative outcomes between patients with and without preoperative tunnel widening. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective analysis was conducted of a large series of consecutive patients undergoing revision ACLR with a minimum follow-up of 2 years. Preoperative tunnel widening was assessed using digital radiographs. All patients underwent single-stage surgery with an outside-in technique, regardless of the degree of tunnel widening. Clinical outcomes were compared according to whether tunnel widening was present (either tunnel ≥12 mm) or not (both tunnels <12 mm). Results: The study included 409 patients with a mean ± SD follow-up of 69.6 ± 29.0 months. After revision ACLR, there was a significant reduction in the side-to-side anteroposterior laxity difference, from 7.7 ± 2.2 mm preoperatively to 1.2 ± 1.1 mm at 2 years ( P < .001). The mean International Knee Documentation Committee (IKDC) and all subscales of the Knee injury and Osteoarthritis Outcome Score (KOOS) exceeded the thresholds for the Patient Acceptable Symptom State defined for primary ACLR. An overall 358 patients had retrievable preoperative radiographs. According to the tunnel diameter measurements, 111 patients were allocated to group A (both tunnels <12 mm) and 247 patients to group B (either/both tunnels ≥12 mm). There were no significant differences between groups with respect to anteroposterior side-to-side laxity difference, graft rupture rates, non–graft rupture related reoperations, or contralateral anterior cruciate ligament injury rates. There was also no significant difference between groups that exceeded minimal detectable change thresholds for any of the PROMs recorded (ACL-RSI [Anterior Cruciate Ligament–Return to Sports After Injury], Lysholm, Tegner, IKDC, KOOS). Conclusion: A single-stage approach to revision ACLR is associated with excellent clinical results when an outside-in drilling technique is utilized. The presence of preoperative tunnel widening does not significantly influence PROMs, knee stability, graft rupture rates, or non–graft rupture related reoperation rates.